REVIEW OF THE PHYTOTHERAPY FOR NEPHROLITHIASIS - Ridwan, Hanna Salwa; Megantara, Sandra; Levita, Jutti (Faculty of Mathematic and Natural Science, Garut University, 2024)
Nephrolithiasis (kidney stone) cases have a prevalence ranging from 1% to 13%. The disease not only hampers kidney function but also elevates the risk of chronic kidney diseases. The pathophysiology of nephrolithiasis is closely linked to elevated concentrations of calcium, oxalate, and/or uric acid in the urine. Pharmacotherapy to manage nephrolithiasis includes thiazide diuretics, allopurinol, citrate supplements, and alpha-blockers that have been prescribed to relieve symptoms. In addition, there is growing interest in exploring the potential of phytotherapy. This review aims to identify suitable phytotherapy approaches by examining relevant articles on nephrolithiasis. The research methodology involved searching PubMed articles using the keywords of ((